Properties of humic substances isolated from different natural sources - Dolmaa, G; Aleksandrova, GP; Lesnichaya, MB; Nominsetseg, B; Ganzaya, G; Bayraa, B; Sukhov, BG; Regdel, D; Trofimov, BA (Mongolian Journal of Chemistry, 2014)
The purpose of study was to determine properties of humic substances by combination of modern and traditional methods. Humic substances isolated from three different sources from Mongolia such as peloid from Lake Gurban nuur, coal from Baganuur deposit and oil shale from Shine khudag deposit. On the basis of determination H/C and O/C atomic ratios in humic substances by elemental analysis, confirmed existing of aromatic structures in the molecules and oxidized functional groups. Have been studied the structure of humic substances by spectral method. For example infrared spectrums showed that humic substances are characterizing with poly-structural components, with different quantity in the samples. Light adsorption of samples in the UV-Vis region, a decrease on the absorption intensity with an increase of the wave length was observed (Fig. 2). The high ratio Н/С, attributed to stretching of C=C bond of aromatic rings in IR spectrums, the high content of functional groups, lower extinction coefficients, confirmed that aromatic fragments to prevail than aliphatic chain fragments in structure of all studied HS. DOI: http://dx.doi.org/10.5564/mjc.v14i0.199 Mongolian Journal of Chemistry 14 (40), 2013, p51-56